2018
DOI: 10.1016/j.jpain.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Estradiol and Testosterone on Stress-Induced Visceral Hypersensitivity in Rats

Abstract: SIVH is more robust in female rats. Estradiol facilitates whereas testosterone dampens the development of SIVH. This could partially explain the greater prevalence of certain chronic visceral pain conditions in women. An increase in spinal BDNF is concomitant with increased stress-induced pain. Pharmaceutical interventions targeting this molecule could provide promising alleviation of SIVH in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 118 publications
4
50
0
Order By: Relevance
“…39 Visceral hypersensitivity induced by stress persisted several weeks in females but only a few days in males, and facilitated by orchiectomy and injection of E2 in males. 26 E2 replacement is an essential factor in increasing the expression of 5-HT 3A receptor in the spinal cord in this study, which is consistent with the observation that the development of somatic hyperalgesia in the E2 + FS group. However, repeated FS alone in this study also induced short period hyperalgesia in rats.…”
Section: Discussionsupporting
confidence: 92%
“…39 Visceral hypersensitivity induced by stress persisted several weeks in females but only a few days in males, and facilitated by orchiectomy and injection of E2 in males. 26 E2 replacement is an essential factor in increasing the expression of 5-HT 3A receptor in the spinal cord in this study, which is consistent with the observation that the development of somatic hyperalgesia in the E2 + FS group. However, repeated FS alone in this study also induced short period hyperalgesia in rats.…”
Section: Discussionsupporting
confidence: 92%
“…The reasons of these gender differences are not completely understood. Gonadal sex hormones such as estradiol seem to enhance sensitivity and pain perception . It is also shown that the menstrual cycle influences IBS symptom occurrence and severity .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in animals have shown that stress increases visceral sensitivity 7,16,22,31,32,46,57,70,71 . The visceromotor response (VMR) is a contraction of core muscles in response to hollow organ distension recorded as a change in magnitude of the abdominal muscle EMG.…”
Section: Introductionmentioning
confidence: 96%
“…It is generally accepted that colonic inflammation following intracolonic administration of exogenous substances (e.g., TNBS, mustard oil, capsaicin) increases the VMR in rats and mice to colorectal distension by sensitizing colonic afferents and visceroceptive dorsal horn neurons 29,33 . Likewise, neonatal stress or chronic stress in adults increases the magnitude of the VMR to visceral stimulation 15,16,31,32,47,57,60 . Stress activates the HPA axis and sympathomedullary axis increasing release of inflammatory mediators in the colon and altering corticotrophin releasing factor (CRF)/CRF receptor signaling, degranulation of mast cells and release of serotonin suggesting stress sensitizes colonic afferents and dorsal horn neurons contributing to visceral hypersensitivity 4,31,55,66 .…”
Section: Introductionmentioning
confidence: 99%